Զանգեզուրը 1920 թ. ապրիլ - օգոստոս ամիսների տարածաշրջանային զարգացումներում - Զուրաբյան, Արշալույս Ա. (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
В апреле 1920-го года после советизации Азербайджана и установления советско-кемалистских отношений, Армения была вынуждена противостоять не только нашествиям Азербайджана, но и агрессии со стороны его союзников: большевистской России и кемалистской Турции. After the sovietization of Azerbaijan in April 1920 and the establishment of Soviet-Kemal political relations, Armenia had to resist not only the attacks of Azerbaijan, but also the military aggression agreed upon by its allies Russia and Turkey.
Keywords: Հայոց պատմություն; Միջազգային հարաբերություններ; Քաղաքականություն